THE EFFECT OF WORK ENVIRONMENT AND WORK SPIRIT ON EMPLOYEE PERFORMANCE AT PT. NADIA BARUNA JAYA - Annisa Nurul Hamidha; Siti Hasbiah; Zainal Ruma; Amiruddin Tawe; Uhud Darmawan Natsir (Journal Management & Economics Review (JUMPER), 2023)
This study aims to (1) determine the effect of the work environment on employee performance (2) determine the effect of morale on employee performance and (3) determine the influence of the work environment and work enthusiasm jointly affect employee performance at PT. Nadia Baruna Jaya. The data used in this research are primary and secondary data with a total sample of 54 respondents. This study used a quantitative approach and was analyzed using multiple linear regression analysis with the help of SPSS data processing to prove the three hypotheses. The results of this study prove that the work environment variable has a significant effect on employee performance with a tcount of3.425> ttable 1.678. the variable of morale has a significant effect with a tcount of 2,529 > ttable of 1,678. It is also known that the independent variables jointly or simultaneously have a positive and significant effect on the dependent variable, namely the performance of employees at PT. Nadia Baruna Jaya. Therefore, if the work environment and morale are continuously improved, it will have an impact on the employee's own performance.